2017
DOI: 10.1016/j.agwat.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal water quality changes in on-farm water storage systems in a south-central U.S. agricultural watershed

Abstract: The objective of this study was to investigate the ability of on-farm water storage (OFWS) systems to mitigate off-site nutrient movement in a south-central U.S. agricultural watershed. We examined the seasonal water quality changes in an OFWS system by measuring several physical and chemical constituents at multiple sampling points throughout the system. Water quality sampling occurred every three weeks during the growing season and every six weeks during the dormant season from February 2012 to December 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Equally in the U.S., habitats that we presently tend to overlook, such as stormwater treatment wetlands, can sometimes be the best available sites for reproduction of amphibians and other species with specific hydrologic needs [89]. Artificial aquatic systems, whether designed for the purpose or not, have improved water quality in critical watersheds like the Mississippi River basin [90][91][92]. Additional examples of ecosystem services provided by artificial aquatic systems appear in Table A1.…”
Section: The Condition Of Artificial Aquatic Systems and Its Driversmentioning
confidence: 99%
“…Equally in the U.S., habitats that we presently tend to overlook, such as stormwater treatment wetlands, can sometimes be the best available sites for reproduction of amphibians and other species with specific hydrologic needs [89]. Artificial aquatic systems, whether designed for the purpose or not, have improved water quality in critical watersheds like the Mississippi River basin [90][91][92]. Additional examples of ecosystem services provided by artificial aquatic systems appear in Table A1.…”
Section: The Condition Of Artificial Aquatic Systems and Its Driversmentioning
confidence: 99%
“…These pollutants can be associated with intensive land use (fertilizers and pesticides) as well as industrial production (waste and sludge). Nitrogen and phosphorus compounds contribute to the eutrophication of water and the deterioration of the quality of aquatic ecosystems [60][61][62]. The negative correlation of the VF1 factor with pH level indicates that when the parameter has low values, carbon and calcium can be released from carbonate rocks.…”
Section: Assessment Of the Temporal And Spatial Variabilitymentioning
confidence: 99%
“…The predictions suggested that substantial reduction in pollutant discharge will not be achieved due to the implementation of source control. -Gutiérrez et al (2017) studied the ability of on-farm water storage (OFWS) systems to mitigate off-site nutrient movement in a south-central U.S. agricultural watershed. They inspected the seasonal water quality changes in an OFWS system by measuring several physical and chemical constituents at multiple sampling points.…”
Section: Source Of Nonpoint Pollutionmentioning
confidence: 99%